Towards reliable identification of male Dicerura: descriptions of three new and seven poorly known species in the Palearctic region (Diptera: Cecidomyiidae, Porricondylinae) - Jaschhof, Mathias; Spungis, Voldemars (Zootaxa, 2018)
The taxonomy of Dicerura Kieffer, 1898, a genus of Porricondylinae now comprising 32 species in the Holarctic region, is revised. Three new species are described based on morphological characters of male adults: D. jakovlevi Jaschhof & Spungis sp. nov. (from Finland), D. penttineni Jaschhof & Spungis sp. nov. (Finland), and D. yezoensis Jaschhof & Spungis sp. nov. (Japan). Dicerura padi Mamaev, 1975 syn. nov. is revealed to be a junior synonym of D. furculata Mamaev, 1968. Seven species, whose original descriptions are from a present-day perspective inadequate for the purpose of identification, are redescribed: D. barbata Mamaev, 1966; D. formosa Mamaev, 1998; D. foliicola Mamaev, 1968; D. furculata; D. iridis (Kaltenbach, 1873); D. stipator Mamaev, 1972; and D. unidentata Spungis, 1987. A key to males of Palearctic Dicerura is provided. New faunistic records are presented for D. barbata; D. complicata Spungis, 1987; D. dentata Spungis, 1979; D. formosa; D. fungicola (Mamaev, 1964); D. mixta Spungis, 1987; and D. unidentata. Male genitalic characters are shown to be useful to a certain extent for structuring the species diversity found within the genus Dicerura. The following groups of species are defined: iridis group (with nine species), dentata group (six species), fungicola group (four species), and formosa group (four species). Six of the species whose morphology is adequately known cannot be grouped within the proposed scheme, indicating the need for further character analysis and continuing search for yet undiscovered species that are assumed to exist in large numbers.